Sets of linear expansions of dynamical systems on a torus for a fixed Lyapunov function - Astaf’eva, M. M.; Stepanenko, N. V. (Ukrains’kyi Matematychnyi Zhurnal, 2007)
We consider sets of linear expansions of dynamical systems on a torus with general alternating Lyapunov function.